THE EFFECTIVENESS OF CO-OP CO-OP METHOD IN TEACHING READING DESCRIPTIVE TEXTS: A CASE OF THE SECOND GRADE STUDENTS OF SMPN 1 KAYEN PATI - Cahya Setiadi (ETERNAL (English Teaching Journal), 2014)
This study is proposed (1) to find out the extent of students reading descriptive texts before and after they are taught using Co-op Co-op method, (2) to find out whether there was a significant different of the students reading comprehension skill before and after they are taught using Co-op Co-op. The type of the research was experiment and methods of collecting data were pre-test and post-test. The population of this study was the second grade students of SMPN 1 Kayen Pati. This study took two classes randomly as the samples. Those were VIIIA as the experimental class and VIIIC as the control class. Each of class had 40 students. Short answer test was used to collect the data. Before the test was given, it was tried out. After the data was computed and it was found out that 20 items were valid. The result of the study shows that students in experimental class who were taught using Co-op Co-op method had better achievement than students in control class who were taught without Co-op Co-op. The average score of pre-test of the experimental class was 71 and post-test was 76. The average score of pre-test of the control class was 70,75 and post-test was 72,75. The pre-test and posttest score then were calculated to get the t-test to know whether there was significant difference between the experimental class and control class. The t-test was 3,108 and t-table was 1,991. Then t-test and t-table were compared. The data shows that t-test was higher than t-table. It means that there was significant difference between the experimental class and the control class. Based on the findings, the students in the experiment group looked more excited with the use of Co-op Co-op in teaching reading descriptive text. In the control class, the writer also found that the students learned and tried to get information of the reading texts individually. Consequently, it affected the students’ achievement in reading descriptive text. Therefore, it can be concluded that Co-op Co-op is an effective method in teaching reading descriptive texts. Thus it is recommended to use Co-op Co-op in teaching reading, especially descriptive text.